“This loose, drifting material of life:” Virginia Woolf’s Diaries and memoirs as Private Epitexts - Annalisa FEDERICI (E-REA)
Virginia Woolf’s literary output is characterised by remarkable homogeneity and coherence between aesthetic principles on the one hand and formal aspects on the other, some qualities which her readers and critics have long recognised, thanks to her diaries, letters and memoirs. A thorough analysis of these texts, which Genette labels “private epitext,” shows that they can be considered as an important creative current parallel to her mainstream criticism and fiction; they also reveal the image of an author for whom life and art were so inextricably interwoven that the creative process enacted in fiction is the object of constant reflection amid the recording of memories, states of mind and daily incidents. The public appearance of the private epitexts has aroused great interest for the insights they afford into Woolf’s life and works, but has also determined a reductive interpretation of them as a mere adjunct to her novels and essays. I argue that Woolf’s private epitexts illustrate the dichotomous vision informing her fiction and aesthetics. As works embodying the Modernist tension between subjectivity and objectivity, the private and the public, they should be considered as a workshop space where Woolf’s aesthetic principles were originally elaborated and as outstanding examples of her creative vein.